Spearhead from Vilkija with Silver-Inlayed Socket - Kazakevičius, Vytautas (Archaeologia Lituana, 2002)
Spearheads decorated with precious and other nonferrous metals are rare finds in Baltic territories. One of them was uncovered by chance in Vilkija (Kaunas district, Lithuania) during soil cultivation works in the autumn of 2000. This was a lanceolate spearhead with a silver encrusted socket.This article is designed to publish the mentioned find, determine its chronology and origin, and review other spearheads with inlayed sockets uncovered in the Baltic territories.The Vilkija spearhead is 22.2 cm long with a 3.2 cm wide lanceolate blade and 2.4 cm diameter silver encrusted socket (Fig. 1). The ornament of the socket represents a horizontally striped composition. It is an arrangement of two similarly patterned stripes composed of 4 recurring “loop” motifs. The design is a geometrical plait of loops interconnected by a stripe interweaved through tabs. It is made by a deep line with opposing notches composing the herring-bone motif (Fig. 1:3).In the material culture of the Baltic tribes, 44 spearheads with sockets encrusted with silver and other nonferrous metals are known. They are of 5 types: III, IVb, E, G and K (according to J. Petersen, 1919 and A. Ruttkay, 1976). The most numerous ones are spearheads of type III (17 items) followed by IVb and E (7 each), G (6) and K (4) (Table 1). The type of one spearhead has not been identified.All these spearheads are decorated with ornaments of three types: 1) geometrical; 2) runic; and 3) striped-weaved or Prussian (Fig. 6).The ornaments of geometrical style are based on strictly geometrical motifs: narrow, horizontal, silver and copper stripes engirdling the sockets, zigzag lines, net and herring-bone motifs, combinations of small prolonged or step-like rhombuses (Fig. 2, 3, 4:2, 3). Sometimes the ornaments of this group are combinations of a few motifs. The lower parts of the sockets often have wider stripes with a more expressive design composed of zigzag or net motifs (Fig. 3). The rest of the socket is decorated with horizontal lines (Fig. 2).The runic ornaments arc based on winding, interweaved lines designed to fom1 fantastic figures (Fig. 4).The striped-weaved or Prussian ornaments arc based on a striped composition of plaits of loops interconnected by a stripe interweaved through tabs (Fig. 5, 6:3). The motif’s of such ornaments are arranged in one, two, three or four lines. The Vilkija spearhead should be ascribed to group 3 (Fig. 6:3).Many spearheads with inlayed sockets have been found with items of richly furnished burials. For this reason they can be rather precisely dated. Moreover, the typological analysis of blade forms and socket ornaments is also chronologically informative. The furnishings of burials – ornaments, other kinds of weapons and riding gear – revealed that spearheads with silver – inlayed sockets are mostly found with “Curonian” type brooches, M type axes, axes with the blade prolonged toward the blunt end, T type, saddle-shaped (type XV; according to A. Ruttkay, 1976) or oval knobs swords, sword chapes belonging to type IV (according to V. Kazakevičius, 1976), stirrups of types III, IV and VII (according to J. Antanavičius, 1976), spurs of types I and III (according to A. Н. Kирпичников, 1973), dirhams and Byzantine coins and other chronologically not well identified items of riding gear as, for example, riding bits, bindings of bridle belts and buckles. All listed artefacts are widespread in the Baltic territory and are virtually dated to the 11th century.It is more difficult to date the spearheads according to their typology. Armourers have constantly sought the most rational forms, size and proportion of spearheads. The spearheads which best answered the military requirements would be rapidly and widely adopted and used for a long time. Therefore, very precise dating is difficult. However, it is obvious that spearheads of types III, IVb, E and G were most widespread and popular among the warriors of the Baltic tribes in the 11th century. The imported K type European spearheads are also dated to the 11th century. The socket ornament of spearheads may serve as a good chronological indicator, particularly if it was widespread and well studied as is the runic type of ornaments. It appeared in Scandinavia in the 11th century and took root in the decorations of various material cultures archeological artefacts. The geometrical ornament is known in different parts of Scandinavia (more widespread in Gotland), Norway, Finland and Estonia.According to the well dated burial items and analogues from Western Europe, the striped-weaved (Prussian) ornament distinguished by the author as typical for the Baltic lands should also be dated to the 11th century. Judging from the burial items and the ornamentation and typology of the spearheads, their use was limited to the 11th century. For this reason, the Vilkija spearhead with a silver – inlayed socket also may be dated to the 11th century and traced to the Prussian lands.